Relevansi Pembelajaran Keterampilan Berbahasa Indonesia Terhadap Literasi Qur’anik - Rissa Shofiani (IEMJ: Islamic Education and Management Journal, 2025)
This study aims to identify the relevance of Indonesian language skills learning to the aspects of literacy taught in the Qur'an. This qualitative study is in the form of a literature study. The research approach uses descriptive analysis. Research data were taken from various relevant journals, books, and scientific articles. Meanwhile, data were obtained through documentation techniques. Furthermore, the analysis includes the stages of reduction, presentation, and conclusion drawing. The results of the study show that Indonesian language skills (listening, speaking, reading, writing) are relevant to the litercay values in the Qur'an, such as the command to listen (QS. Al-Mulk:10), speak with six qaulan, read (QS. Al-'Alaq:1–5), and write (QS. Al-'Alaq:4–5). This research contributes to the integration that affirms the importance of language skills learning, which also has a theological basis in Islamic teachings.